2022
DOI: 10.3389/fphy.2022.986605
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric evolutionary game analysis of emergency cooperative social networks for magnitude emergencies: Evidence from the Beijing-Tianjin-Hebei region in China

Abstract: Emergency cooperative social networks (ECSNs) play a very important role in emergency management for magnitude emergencies in China recently. Based on the data set of cooperative fight against COVID-19 of the Beijing-Tianjin-Hebei region in China, using social network analysis (SNA) and asymmetric evolutionary game model, this study finds that the asymmetry between regions is comprehensively determined by resource endowment, administrative level, geographical distance, regional vulnerability, political pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Besides, SNA has been applied to identify the key risk factors in construction projects in high-density urban areas (Yuan et al , 2018), the construction phase of the metro (Lu and Zhang, 2020) and green redevelopment projects of industrial brownfields (Zhang et al , 2023). Moreover, Nan and Wang (2022) conducted SNA and found that the asymmetry of emergency cooperative social networks between regions was comprehensively determined by multiple factors, of which political factors were very important. Additionally, SNA expanded the approaches to examining the effectiveness of interproject communication management (Plokhov et al , 2016) and e-business standards consortia (Choi et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, SNA has been applied to identify the key risk factors in construction projects in high-density urban areas (Yuan et al , 2018), the construction phase of the metro (Lu and Zhang, 2020) and green redevelopment projects of industrial brownfields (Zhang et al , 2023). Moreover, Nan and Wang (2022) conducted SNA and found that the asymmetry of emergency cooperative social networks between regions was comprehensively determined by multiple factors, of which political factors were very important. Additionally, SNA expanded the approaches to examining the effectiveness of interproject communication management (Plokhov et al , 2016) and e-business standards consortia (Choi et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%